Meningkatkan Kualitas Pembelajaran di Sekolah Dasar melalui Metode Aktif dan Inovatif - Ayesha Malika Salsabilla; Intan Nur Cahya; Tasya Latipah; Oman Farhurohman (Lembaga Yasin AlSys, 2025)
The quality of learning at the elementary school level in Indonesia continues to face various challenges, one of which is the dominance of traditional teacher-centered instructional methods, resulting in low student motivation, participation, and critical thinking skills. This study aims to explore and analyze the effectiveness of implementing active and innovative learning methods that are relevant in the context of primary education to enhance learning quality. A library research method was employed by analyzing various scholarly articles and documents related to active and innovative learning in elementary schools. The findings indicate that instructional strategies such as Project-Based Learning, Problem-Based Learning, Discovery Learning, and cooperative approaches like Think-Pair-Share have proven effective in improving learning outcomes, critical thinking skills, creativity, and student motivation. Additionally, the integration of technology through interactive digital media and gamification approaches also contributes positively to increased student participation and the creation of an enjoyable learning environment. These results affirm that active and innovative learning plays a significant role in improving the quality of primary education. The study recommends ongoing teacher training and the provision of supporting facilities as essential prerequisites to ensure that student-centered methods are implemented effectively within Indonesia’s basic education system.